lndigenous concept of intelligence in Mexican ethnic groups - Figueroa Cuevas, Joaquín (2004)
Three studies were conducted to explore the notion of intelligence in Mexican ethnic groups. Results of the first study showed that mestizo and nahua teachers defined child intelligence in technological terms, as in industrialized countries. However, indigenous teachers, defining intelligence from the ethnic viewpoint, stressed its social in the same proportion as its technological aspects. In the second study, the concept of intelligence of nahua mothers emphasized the importance of social aspects of intelligence. In the third study, bilingual teachers from different ethnic regions defined intelligence in equivalent terms as nahua teachers from the first study. Conclusions from the three studies point to a concept of intelligence related to the leve! of cultural contact of the person defining it.